Treatment of Biodiesel Wastewater using Ferric Chloride and Ferric Sulfate - Daud, Zawawi; Nasir, Nazlizan; Abd Kadir, Aeslina; Abdul Latiff, Ab Aziz; Ahmad, Baharin; Suhani, Noorain; Awang, Halizah; Abdul Halim, Azhar (International Journal of Integrated Engineering, 2017)
Abstract: The production of biodiesel through the transesterification method produces a large amount of wastewater that contains high level of chemical oxygen demand (COD) and oil and grease. In this study, coagulation was adopted to treat the biodiesel wastewater. Two types of coagulants were examined using standard jar test apparatus, i.e. ferric chloride and ferric sulfate. The effects of pH and coagulant dosage were examined at 150 rpm of rapid mixing and 20 rpm slow mixing and 30 min settling time, higher removal of SS (over 80%), color (over 80%), COD (over 50%) and Oil and Grease (over 90%)Â  were achieved at pH 6.Â  Ferric Chloride was found to be superior was observed at reasonable lower amount of coagulant i.e. 300 mg/L. The result indicated that coagulation and flocculation process had contributed bigger roles in integrated treatment system.Â